2021
DOI: 10.1159/000514269
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Home-Based Exercise Program on Indices of Physical Function and Quality of Life in Elderly Maintenance Hemodialysis Patients

Abstract: <b><i>Background:</i></b> Patients on maintenance hemodialysis (MHD) exhibit muscle wasting and impaired physical function which can be reversed with regular exercise, but accessibility to exercise programs for this unique population is lacking. We assessed the efficacy of a home-based exercise program on a broad range of indices of physical function, quality of life (QoL), and cognitive decline in patients with MHD. <b><i>Design and Methods:</i></b> Twenty-eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 68 publications
0
31
0
3
Order By: Relevance
“…There were five studies out of the 21 included in a meta-analysis that showed an increase in the SF-36 physical component score after exercise training, with a mean increase of 10%. In spite of the fact that the overall SF-36 physical component score changed little, the exercise group's physical component score increased by 43% [74].…”
Section: Physical Function and Qolmentioning
confidence: 82%
See 1 more Smart Citation
“…There were five studies out of the 21 included in a meta-analysis that showed an increase in the SF-36 physical component score after exercise training, with a mean increase of 10%. In spite of the fact that the overall SF-36 physical component score changed little, the exercise group's physical component score increased by 43% [74].…”
Section: Physical Function and Qolmentioning
confidence: 82%
“…The SF-36 domains of physical functioning, role physical, and role emotional all increased over time as a result of exercise training, resulting in remarkable improvements in overall health. After the exercise intervention, all five dimensions of Kidney Disease Quality of Life improved [74]. The EXITE (Exercise Introduction to Enhance Dialysis Performance) experiment found that MHD patients' functional status improved after a simple, personalised six-month home-walking programme.…”
Section: Physical Function and Qolmentioning
confidence: 99%
“…Reasons for their exclusion included the following: not including hypertensive participants and/or participants that were on antihypertensive medication (n = 333); not including a physical exercise intervention nor physical activity recommendation (n = 56); not including blood pressure self-management (n = 4); not including a lifestyle change intervention (n = 2); not including the delivery of health services via remote telecommunications (n = 3); not including an exercise physiologist, physical therapist, physiotherapists or a certified trainer supervision (n = 49). Finally, 19 articles were included in this systematic review [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], as shown in Figure 1. Two of the studies were carried out by the same first author [21,22], and despite some overlapping data as a result of a common prospective randomized controlled trial, the sample and main outcomes are different.…”
Section: Identification and Study Selectionmentioning
confidence: 99%
“…physiotherapists or a certified trainer supervision (n = 49). Finally, 19 articles were cluded in this systematic review [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], as shown in Figure 1. Two of the studies we carried out by the same first author [21,22], and despite some overlapping data as a res of a common prospective randomized controlled trial, the sample and main outcomes a different.…”
Section: Identification and Study Selectionmentioning
confidence: 99%
“…Estes pacientes, por vezes, têm redução da mobilidade e dificuldades de transporte. Tais situações de privação da realização de atividades físicas têm demonstrado impacto negativo em sua qualidade de vida (MYERS et al, 2021).…”
Section: Fundamentação Teóricaunclassified